How work ethics, workload, and work motivation contribute to work commitment: a study among the service company employees in the Klang Valley, Malaysia - Mohamat Nor, Nur Shahida; Marof, Aini Azeqa; Sulaiman, Abdul Hadi (Human Resource Management Academic Research Society, 2023)
In a rapidly evolving global market, understanding the factors that influence employee commitment in courier services is essential for maintaining a competitive edge. Despite limited empirical research, the work commitment of employees in courier service companies plays a critical role in logistics and supply chain sectors. This study examines the relationship between work ethics, workload, work motivation, and organizational commitment among courier service employees in the Klang Valley, Malaysia. Using homogenous convenience sampling, the study involved 382 respondents from various companies. Data was collected through an online questionnaire using established metrics: Organizational Commitment Questionnaire, Short-form Multidimensional Work Ethic Profile, Quantitative Workload Inventory, and the Multidimensional Work Motivation Scale. Descriptive statistics, Pearson correlation, and multiple regression analyses were employed for data evaluation. The findings indicate that a majority of respondents exhibited high levels of work ethics, workload, and organizational commitment, but moderate levels of work motivation. Significant correlations were identified between the variables and organizational commitment, with work ethics emerging as the most substantial predictor. this study not only fills a gap in the empirical research concerning employee commitment in the logistics sector but also offers practical implications for courier service companies. It emphasizes the necessity of cultivating strong work ethics and provides a foundation for developing targeted strategies to increase work motivation. Such insights are critical for companies aiming to enhance their competitive position in the global market by capitalizing on the commitment of their workforce.